Contribution of Brain Processes to Tissue Loss After Spinal Cord Injury: Does a Pain-Induced Rise in Blood Pressure Fuel Hemorrhage? - Fauss, Gizelle N. K.; Strain, Misty M.; Huang, Yung-Jen; Reynolds, Joshua A.; Davis, Jacob A.; Henwood, Melissa K.; West, Christopher R.; Grau, James W. (Frontiers in Systems Neuroscience, 2021)
Pain (nociceptive) input soon after spinal cord injury (SCI) expands the area of tissue loss (secondary injury) and impairs long-term recovery. Evidence suggests that nociceptive stimulation has this effect because it promotes acute hemorrhage. Disrupting communication with the brain blocks this effect. The current study examined whether rostral systems exacerbate tissue loss because pain input drives an increase in systolic blood pressure (BP) and flow that fuels blood infiltration. Rats received a moderate contusion injury to the lower thoracic (T12) spinal cord. Communication with rostral processes was disrupted by cutting the spinal cord 18 hr later at T2. Noxious electrical stimulation (shock) applied to the tail (Experiment 1), or application of the irritant capsaicin to one hind paw (Experiment 2), increased hemorrhage at the site of injury. Shock, but not capsaicin, increased systolic BP and tail blood flow in sham-operated rats. Cutting communication with the brain blocked the shock-induced increase in systolic BP and tail blood flow. Experiment 3 examined the effect of artificially driving a rise in BP with norepinephrine (NE) in animals that received shock. Spinal transection attenuated hemorrhage in vehicle-treated rats. Treatment with NE drove a robust increase in BP and tail blood flow but did not increase the extent of hemorrhage. The results suggest pain input after SCI can engage rostral processes that fuel hemorrhage and drive sustained cardiovascular output. An increase in BP was not, however, necessary or sufficient to drive hemorrhage, implicating other brain-dependent processes.